Peningkatan Minat Dan Partisipasi Anak-Anak Untuk Belajar Baca Al-Qur’an Di Markas Talaqqi Talaqqi Al Athfal (MTA) Medan - Mutiara Siahaan; Ahmad Afandi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This community service activity is based on an understanding of the importance of religious education and the formation of a Qur'anic generation from an early age. Reading and memorizing the Qur'an is an effective method to ensure that the younger generation has a strong understanding and deep connection with the holy book of Islam. In addition, it also helps to form individuals who are committed to religious teachings and have good morality This activity was conducted in several stages, namely the preparation, implementation, and evaluation stages. The preparation stage included observations and interviews to identify the problems faced. The results of the observation showed that the management of Markaz Talaqqi Al Athfal had difficulty in encouraging the interest and participation of children in Pasar I, Jl. Setia Budi, Tj. Sari, Kec. Medan Selayang, Medan City, North Sumatra to read the Qur'an. To overcome this challenge, efforts were made to increase the interest and participation of children in the Markaz Talaqqi Al Athfal, totaling 22 people. This was realized through the implementation of outbound activities and giving rewards to children, with the aim of increasing their enthusiasm in learning the Qur'an. Evaluation was carried out after the activity was completed, and the results showed that the children at Markaz Talaqqi Al Athfal were very enthusiastic in participating in each activity. This enthusiasm can be seen from the participation and interest in learning the Quran which is increasing day by day. The children's parents also feel helped and happy to see the children's participation in the activities.